Analisis Yuridis Perjanjian Sewa Menyewa Dengan Objek Tanah Antara Warga Negara Indonesia Dengan Warga Negara Asing: (Studi Putusan Nomor 299/Pdt.G/2021/PN.Mtr) - Muhammad Azzura Notariano; Arief Rahman (Fakultas Hukum Universitas Mataram, 2023)
This study aims to determine the legal considerations of the panel of judges in the Mataram District Court Decision Number 299/Pdt.G/2021/PN.Mtr and the defendant's liability in the land lease agreement which is the land owned by the plaintiff. The method used by the researcher in this study is a normative legal research method using the approach of legislation, conceptions and cases. The results of the study were the panel of judges stated that the defendant was proven to be in default, the agreement could be canceled and the object was transferred back to the plaintiff. And the Defendant must pay compensation as a liability